How is small bowel permeability in endometriosis patients? a case control pilot study. (1st November 2020) - Viganó, D.; Zara, F.; Pinto, S.; Loddo, E.; Casula, L.; Soru, M. B.; D'Ancona, G.; D'Alterio, M. N.; Giuliani, C.; Angioni, S.; Usai, P.
Abstract: Endometriosis is a chronic inflammatory disease of women of reproductive age. Small bowel (SB) permeability and lipopolysaccharides (LPS) could play a role in the perduration of low grade inflammation status and the pathogenesis of endometriosis. To clarify this hypothesis, we measured SB permeability through plasma values of LPS and urinary secretion of lactulose (La), mannitol (Ma) and their ratio (L/M) in patients with endometriosis compared with healthy controls (HC). Eight patients and 14 HC entered the study. SB permeability was evaluated by high-performance liquid chromatography of urine concentrations of La and Ma. Plasma levels of LPS were measured in the blood. Moreover, a nutritional, gastroenterological, quality of life evaluation was performed through validates questionnaires and complete gynaecological evaluations. The statistical analysis of the obtained data did not show differences in anthropometric and nutritional characteristics and gastrointestinal functional disease in the two groups. Patients reported higher levels of pelvic chronic pain (3.87 ± 2.99 vs 0.15 ± 0.55; pe = 0.001) and significantly higher LPS plasma levels (0.529 ± 0.11 vs 0.427 ± 0.08; p value = .027) than HC. Our results indicate that intestinal permeability is abnormal in endometriosis patients, and it might play a role in the pathogenesis of this chronic disease.